Analysis of Work-Life Balance in Improving Employee Productivity at Legok Community Health Center, Tangerang Regency - Arief Budi Santoso; Listiawati Listiawati (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the role of work-life balance in improving employee productivity at Legok Community Health Center, Tangerang Regency. The demanding nature of primary healthcare services requires employees to balance professional duties with personal and family responsibilities. Failure to maintain this balance may increase fatigue, stress, and burnout and may reduce service quality. The study used a qualitative descriptive design to obtain an in-depth understanding of employees' experiences. Data were collected through direct observation, Focus Group Discussion-based in-depth interviews, and documentation. Five informants were selected purposively, consisting of the Head of the Administration Sub-Section as the key informant and four supporting informants representing different professional roles. Data were analyzed using the interactive model of Miles and Huberman through data collection, data reduction, data presentation, and conclusion drawing. Source, method, time, and theoretical triangulation were applied to strengthen data credibility. The findings show that employees generally experience a satisfactory work-life balance across the dimensions of time balance, involvement balance, and satisfaction balance. Nevertheless, several challenges remain, including shift work, service-related communication outside regular working hours, program deadlines, and limitations in time management and internal coordination. Employee productivity is relatively high because it is supported by professional competence, work commitment, teamwork, and continuous training provided by the health center and local government. The study concludes that work-life balance supports employee productivity and service quality. Therefore, clearer communication boundaries, healthier work arrangements, improved scheduling, and stronger coordination are needed to sustain employee well-being and organizational performance.